The immunosuppressive mechanisms induced by sepsis and the corresponding treatment strategies - Gao, Qinfen; Teng, Yajun; Zhu, Ling; Zhang, Wei; Li, Zengzheng (Frontiers in Immunology, 2025)
Sepsis is a life-threatening organ dysfunction caused by the dysregulation of the body’s response to infection. It is characterized by a high incidence, high mortality rate, and high medical burden, and is a major global health threat. Although updated treatment guidelines have reduced the mortality rate during the acute phase, survivors still face a high long-term risk of recurrent infection and death. Recent studies have shown that the long-term high mortality rate of sepsis is closely related to the immunosuppression it induces. Sepsis-induced immunosuppression originates from the disruption of immune homeostasis, characterized by excessive release of anti-inflammatory cytokines, increased apoptosis of immune cells (especially lymphocytes), T cell exhaustion, and expansion of immune regulatory cells (Tregs, MDSCs). Reduced expression of human leukocyte antigen-DR (HLA-DR) and upregulated expression of immune checkpoint molecules (PD-1, CTLA-4, TIM-3, etc.) further exacerbate immunosuppression. This article systematically reviews the immune imbalance state and related mechanisms of patients with sepsis, and summarizes new immunotherapy strategies such as immune stimulatory factors (GM-CSF, IL-7, IL-15), immune checkpoint inhibitors (anti-PD-1/PD-L1, anti-CTLA-4, anti-TIM-3), and emerging therapies (mesenchymal stem cells, calprotectin inhibitors, TREM-1 inhibitors). The aim is to enhance clinicians’ understanding of sepsis-induced immunosuppression, facilitate early intervention, and reduce the incidence and mortality of long-term complications.